QUALITY OF LIFE AMONG HAEMODIALYSIS PATIENTS IN A DIALYSIS CENTRE IN THE NORTHERN REGION OF SARAWAK - Dorinna anak Ngalai; Osman Ali (Asian Journal of Medicine & Health Sciences, 2019)
Background: Haemodialysis has been known to affect the patient’s quality of life (QOL). The procedure may affect the social life and economic status of the sufferer. Aim: To determine the quality of life among haemodialysis patient at Northern Region of Sarawak. Methodology: The cross-sectional study was conducted among 100 chronic renal failure patients registered at the haemodialysis centre at Miri Red Crescent Dialysis Centre in Northern Region of Sarawak. Their quality of life (QOL) was measured using Kidney Disease Quality of Life-Short Form (KDQOL-SF) instrument, which measures the disease, physical and mental components of QOL. Results: Overall score for three components of the KDQOL-SF was 69.1. The score of each component were 66.3, 52.6, and 39.4 respectively. There were statistically significant association between marital status and physical health component (P=0.046); age and physical health component (P=0.026); educational level and mental health component (P=0.006). Conclusion: In general, QOL of patients on dialysis in this centre was good. Most of the patients had better quality of life in the kidney disease component, and mental health component, despite of having poor quality of life in the physical health component. QOL of patients will be better if they got encouragement from dialysis staff in the Centre, getting strong social support from the family and if they actively involved in social function.